AL-JAMI’AH : Islam and Local Politics: In the Quest of Kyai, Politics, and Development in Kebumen, 2008-2010 - Laila Kholid Alfirdaus (State Islamic University (UIN) Sunan Kalijaga, 2013)
The involvement of kyai (religious teacher) in political affairs has become prominent after the Indonesia reformation. With his charismatic images and long-maintained religious authority, kyai has amount of capital to easily enroll his self into politics without significant barriers. This becomes more evidence in the Indonesian political sphere after the reformation as the number of kyais serving as leaders in bureaucracy is increasing.